The novel antidiabetic medications on diabetic retinopathy: relevant molecular mechanisms, advancing diagnostic innovations, and therapeutic implications - Wen, Song; Xu, Chenglin; Yuan, Yue; Chen, Lijiao; Ren, Yishu; Xu, Zhimin; Jin, Jianlan; Li, Jiyu; Zhou, Ligang (Frontiers in Medicine, 2026)
Diabetic retinopathy (DR), a major cause of vision loss in working-age adults, manifests as a microvascular complication of diabetes, with early-stage non-proliferative diabetic retinopathy (NPDR) requiring timely intervention. This review explores the molecular mechanisms underlying early DR, including microvascular damage, inflammation, oxidative stress, and advanced glycation end products, with distinct profiles in type 1 and type 2 diabetes. Novel antidiabetic medications, such as GLP-1 receptor agonists, SGLT-2 inhibitors, and dual GIP/GLP-1 agonists, target these pathways, may have potential to reduce NPDR progression expected in clinical trials. Advanced diagnostics, including ultra-widefield fundus photography, OCT, OCTA, and AI-based algorithms, achieve over 95% accuracy in detecting NPDR and predicting systemic risks like cardiovascular disease. This article highlights the therapeutic implications of novel antidiabetic drugs, advocating for integrated diagnostic and treatment strategies to mitigate DR's global burden and preserve vision.